호주 초등 수학과 교육과정에서의 디지털 소양 분석 - 박미미(Mimi Park) (수학교육철학연구, 2024)
2022 개정 교육과정에서는 디지털 소양을 기초 소양의 하나로 설정하고 모든 교과에서 디지털 소양의 함양을 도모하고 있으나, 수학과 교육과정에서 수학 교과 내용과 디지털 소양 간의 연계성을 파악하기는 어려운 실정이다. 이에 이 연구에서는 교과 내용과 역량을 명시적으로 연계하고 있는 호주의 교육과정에서 일반 역량으로 제시된 디지털 소양의 특징을 이해하고, 호주 초등 수학과 교육과정에서 디지털 소양의 반영 양상을 분석하였다. 분석 결과, 호주의 초등 수학과 교육과정에서는 디지털 소양의 하위 요소 중 ‘도구 선택 및 조작’, ‘데이터 해석’, ‘생성, 의사소통 및 협력’, ‘데이터 수집 및 획득’의 네 가지가 주로 반영되었고, 내용 영역별로 디지털 소양의 하위 요소가 다르게 반영되어 있음을 확인하였다. 이를 기반으로 우리나라 수학과 교육과정에서 기초 소양으로서 디지털 소양의 함양을 추구하기 위한 방안에 대한 시사점을 제공하였다. The 2022 revised curriculum in Korea presented digital literacy as a fundamental skill and emphasized its development across all subjects. However, establishing a clear connection between mathematics content and digital literacy within the mathematics curriculum remains challenging. This study aims to elucidate the concept of digital literacy as outlined in the general capabilities of the Australian curriculum and to examine its integration within the F-6 Australian mathematics curriculum. Findings revealed four sub-components of digital literacy embedded within the Australian elementary mathematics curriculum, with variations in prominence across different mathematics content areas. Drawing from these results, recommendations are provided for fostering digital literacy as a fundamental skill within mathematics curriculum. KCI Citation Count: 1